Exploring functional relationships to foster algebraic thinking in grade 8 - Matos, Ana (2011)
This article aims to identify the contributions of a teaching unit in fostering grade 8 students’ algebraic thinking. The unit is based on exploratory and investigation tasks about functional relationships. Using a qualitative and interpretative methodology, data collection included participant observation of classes by the teacher, registered in her professional journal, and gathering written records from students. Results indicate that working in the proposed tasks and combining students’ group work with classroom discussions promoted the development of meaning for the algebraic language. The work in this unit also encouraged the students to widen the number of strategies that they used to explore situations involving relations between variables, to reason in a more general way, and to express their generalizations using a formal language.